2017
DOI: 10.1093/ntr/ntx218
|View full text |Cite
|
Sign up to set email alerts
|

HIV Care Initiation: A Teachable Moment for Smoking Cessation?

Abstract: This study documents significant increases in intention to quit smoking in the 3-month period following HIV care initiation. Moreover, quit intention trended downward following the 3-month follow-up until the 12-month follow-up. In addition, a marked effect for HIV disease stage was observed, whereby participants with advanced HIV disease (vs. those without) experienced a greater increase in intention to quit. HIV treatment initiation appears to be associated with increases in intention to quit smoking, thus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
(36 reference statements)
3
13
0
Order By: Relevance
“…Wu et al [40] reported that smokers had twice the risk of fracture compared to non-smokers. Smoking cessation programs among smokers with HIV may reduce fracture risk after just three months [41]. The HCV co-infection risk, with pooled aHR of 1.6, confirms the findings of Dong et al's meta-analytic study.…”
Section: Plos Onesupporting
confidence: 76%
“…Wu et al [40] reported that smokers had twice the risk of fracture compared to non-smokers. Smoking cessation programs among smokers with HIV may reduce fracture risk after just three months [41]. The HCV co-infection risk, with pooled aHR of 1.6, confirms the findings of Dong et al's meta-analytic study.…”
Section: Plos Onesupporting
confidence: 76%
“…Furthermore, this secondary analysis supports and builds upon our previous findings suggesting that disease status impacts smoking behaviors (Vidrine et al, 2017). Variables known to modulate the relationship between disease status and smoking behaviors, such as symptom burden and nicotine dependence, may underlie this relationship.…”
Section: Discussionsupporting
confidence: 84%
“…In fact, intention to quit smoking may increase upon the onset of HIV or an advancement in disease progression. Our previous work (Vidrine et al, 2017) observed increased intention to quit and abstinence among HIV-positive cigarette smokers with advanced disease stage, in comparison to those with no advanced HIV, at three and six-month post-diagnosis follow-ups. This research suggests that events/stages of HIV may serve as a teachable moment, defined as an event that can prompt individuals to adopt risk-reducing behaviors.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…These include the provision of very brief advice (VBA) by healthcare workers (a brief structured intervention consisting of assessing smoking behaviours and providing advice and specific recommendations to support smoking cessation), nicotine replacement therapy, prescription of bupropion or varenicline and use of stop smoking clinics 10. To date, few studies have assessed these interventions in the context of HIV care services and none have done so in the UK 11. We sought to evaluate the impact of asking healthcare workers to systematically identify current smokers attending routine HIV ambulatory care appointments and provide VBA.…”
Section: Introductionmentioning
confidence: 99%